2018
DOI: 10.14814/phy2.13872
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation time course and neuromuscular fatigue during repeated cycling sprints with bilateral blood flow restriction

Abstract: The aim was to evaluate changes in peripheral and cerebral oxygenation, cardiorespiratory, and performance differences, as well as neuromuscular fatigue across multiple levels of blood flow restriction (BFR) during a repeated cycling sprint test to exhaustion (RST). Participants performed three RST (10‐sec maximal sprints with 20‐sec recovery until exhaustion) with measurements of power output and V̇O2peak as well as oxygenation (near‐infrared spectroscopy) of the vastus lateralis and prefrontal cortex. Neurom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(109 citation statements)
references
References 56 publications
12
96
1
Order By: Relevance
“…As previous research has demonstrated, these hypoxia and BFR conditions induce large increases in deoxygenation of the legs (probably due to a large amount of active muscle mass). 2,22 Additionally, it has been shown that legs are quite responsive (greater changes in perfusion) during systemic hypoxia 22 and BFR conditions, 2 as is substantially confirmed to a greater extent in the present study of the arms. Collectively, this demonstrates that there are differing vascular properties and responses between limbs.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…As previous research has demonstrated, these hypoxia and BFR conditions induce large increases in deoxygenation of the legs (probably due to a large amount of active muscle mass). 2,22 Additionally, it has been shown that legs are quite responsive (greater changes in perfusion) during systemic hypoxia 22 and BFR conditions, 2 as is substantially confirmed to a greater extent in the present study of the arms. Collectively, this demonstrates that there are differing vascular properties and responses between limbs.…”
Section: Discussionsupporting
confidence: 85%
“…After critical assessment of number of sprints, power output, torque factor, pedaling frequency, and perceived effort during piloting sessions with arm cycling and RST, the percentage for BFR and resistance for arms were chosen. 2 During familiarization, anthropometric data were measured and the informed consent and health questionnaire [Physical Activity Readiness Questionnaire, PAR-Q & YOU, 13 were completed. Participants donned the BFR cuff (custom-made 4 x 70 cm cuff, 3 × 41 bladder; D.E.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yanagisawa and Fukutani demonstrated that the total hemoglobin/myoglobin concentration significantly increases during exercise with BFR [36], likely because of the impeded venous outflow. Along this line of reasoning, Willis and colleagues reported greater positive changes in tissue perfusion (via blood volume, Δ [THb]) during repeated cycling sprints with BFR compared to non-restricted repeated sprints [46]. Performing BFR during exercise also appears to affect muscle oxygenation.…”
Section: Discussionmentioning
confidence: 99%